A simulation study on fire safety aspects of rock cavern accommodating high occupant load. (September 2020) - Tsang, H.L.; Fong, N.K.; Chow, W.K.
Highlights: Feasibility of utilizing rock caverns for housing high occupant loads was explored. Fire safety strategies of the existing overseas rock cavern projects were discussed. Evacuations for an overseas rock cavern at its designed maximum value were simulated. Effects of different fire locations and occupant loadings were studied numerically. Time to reach tenability limits for different scenarios were compared. Abstract: Rock caverns are heralded as the next frontier in metropolitan development around the world as the likes of Hong Kong striving to plough through continuous urbanization without undue sacrifices in health and safety. Meanwhile, the use of underground space in densely developed urban areas such as Hong Kong will offer good opportunities for creation of space, enhancement of connectivity and improvement of the urban environment. Underground space can also be used to house new facilities or relocate existing above-ground facilities that are incompatible with the urban setting, thereby releasing valuable surface land for other beneficial and compatible land uses. Generally speaking, a number of natural and man-made disasters such as fire, explosions, earthquakes, and flood are factored into the design of cavern and underground space. By far, fire is the most serious concern due to its associated risks in evacuation difficulties, barriers to fire service intervention, lack of natural ventilation, and the reliability of power supplies. In this connection, the existing rock caverns in Hong Kong were not designed for accommodating high occupant loads. On the other hand, in accordance with the strategic planning of rock cavern development in Hong Kong, facilities intended for accommodating high occupant load such as indoor sports hall and museum are recommended to be relocated to rock cavern. To this end, key scientific criteria affecting fire phenomena in rock cavern such as potential fire size, occupant load, geometry, location and topography, etc. of the rock caverns and their corresponding effects should be identified and studied so as to address the said inherent risks and formulate a secure fire safety design. This paper aims at exploring the feasibility of the rock caverns to be utilized as space for accommodating high occupant loads in Hong Kong. The policy and direction of the rock cavern development in Hong Kong are introduced. The inherent risks of rock caverns and underground space in relation to fire safety are elaborated as well. Fire safety strategies of some existing overseas rock cavern projects accommodating high occupant load are discussed. The evacuation situations for an overseas rock cavern at its designed maximum and different occupant loadings were also simulated. In addition, the effects of different fire locations, heat release rates and occupant loadings at three types of access tunnel, namely, horizontal, ascending, and descending tunnels leading to a cubic cavern space were studied using a Computational Fluid Dynamics (CFD) based software, the Fire Dynamics Simulator (FDS), as well. The time to reach tenability limits and predicted total evacuation time for different scenarios are compared and analyzed. Various correlations of key scientific criteria affecting fire phenomena in rock cavern are identified and discussed. Subsequently, according to the predicted results, recommendations in terms of fire safety considerations on relocating public utilities with high occupant load into caverns are recommended.